Human Resources Performance Improvement Through Motivation, Disipline, Work Environment, and Commitment in PT. Supra Matra Abadi PMKS Aek Nabara - Lily Alpya; Elvina Elvina; Mulya Rafika (PT Mattawang Mediatama Solution, 2022)
The purpose of this study was to determine the improvement of human resource performance through motivation, work environment discipline and commitment at PT. Supra Matra Abadi PMKS Aek Nabara. The data used in this study is primary data by distributing questionnaires to employees of PT. Supra Matra Abadi PMKS Aek Nabara, Bilah Hulu District, Labuhanbatu Regency. The population in this study was 250 employees. Based on the Slovin formula, the sample size in this study was 89 people as respondents. distribution of questionnaires will be conducted on employees of PT. Supra Matra Abadi PMKS Aek Nabara, Bilah Hulu District, Labuhanbatu Regency. The data is processed in the form of numerical data (numbers) using a Likert scale. Data collection methods in this study were interviews and questionnaires. The data is processed using spss for windows version 20.0. method of data analysis using quantitative methods, namely by using multiple linear regression analysis. The results of the study prove that three variables, namely Motivation, Work Environment Discipline and Commitment have a significant influence on the defended variable, namely the Improvement of Human Resources Performance at PT. Supra Matra Abadi PMKS Aek Nabara.